Assessment of disease activity in patients with rheumatoid arthritis using plasma tumour M2-pyruvate kinase test - Ahn, Sung Soo; Kim, Hye Min; Park, Younhee (Frontiers in Immunology, 2022)
Background: Pyruvate kinase M2 (PKM2) is an enzyme that regulates the final process of glycolysis and exists in tetrameric and dimeric forms. The dimeric form of PKM2, also known as tumour M2-PK, increases when aerobic glycolysis is augmented, a feature observed in rheumatoid arthritis (RA). We investigated whether plasma tumour M2-PK is elevated in patients with RA and whether its levels correlate with disease activity. Methods: Plasma levels of tumour M2-PK were measured for patients with RA (n=151), those with osteoarthritis (OA) (n=37), and controls (n=37). We evaluated the association between plasma tumour M2-PK and continuous variables using Pearson’s correlation analysis, and multivariate logistic regression analysis to determine the association between plasma tumour M2-PK and disease activity status. Knee synovial tissue blocks from patients with RA and OA were subjected to real-time quantitative PCR (qPCR) using two different primers for PKM2 and tumour M2-PK immunohistochemical (IHC) staining. Results: The tumour M2-PK level significantly correlated with the disease activity score in 28 joints (DAS28)-erythrocyte sedimentation rate (ESR) (r=0.546, p<0.001) and DAS28-C-reactive protein (CRP) (r=0.589, p<0.001). Moreover, repeat testing of tumour M2-PK levels in 20 patients revealed a significant decline in tumour M2-PK levels after reduction in inflammation (p<0.001). Area under the receiver operating characteristic curve (AUROC) analysis demonstrated that upon incorporation of tumour M2-PK, ESR, and CRP, the area under the curve was 0.962 for distinguishing moderate/high from remission/low disease activity. Adjusted logistic regression also revealed that a tumour M2-PK >43.9 U/mL (OR 3.672, p=0.042) independently predicted moderate/high disease activity status. Furthermore, tumour M2-PK levels in patients with RA were significantly higher than in those with OA and controls (all p<0.001). However, no differences were found in PKM2 expression in RA and OA synovial tissues as assessed by qPCR, and IHC analysis revealed negligible tumour M2-PK expression in the synovial tissues. Conclusion: Circulating plasma tumour M2-PK levels may be a clinically useful indicator for evaluating disease activity and RA diagnosis.